2020
DOI: 10.5802/crchim.9
|View full text |Cite
|
Sign up to set email alerts
|

Pt(II) complex of Schiff base derived from L-phenylalanine and furfuraldehyde in the presence of 8-hydroxyquinoline: Structural analysis, composition of complex and biological activity

Abstract: In the present study, we synthesized a Schiff base (L 1) derived from L-phenylalanine with furfuraldehyde and its Pt(II) complex ([Pt(L 1)(L 2)]: [Pt(N-(furfuralidene)phenylalanine)(8hydroxyquinoline)]) in the presence of 8-hydroxyquinoline (L 2). The chemical structures of the synthesized Schiff base and Pt(II) complex were characterized using ESI-MS, UV-Visible, FT-IR, 1 H NMR, 13 C NMR, and powder-XRD spectroscopy. The surface morphologies and elemental composition were determined by SEM and EDX. Thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…Furthermore, the shift in signals and splitting of protons of the aryl groups were observed, especially in the spectrum of Zn[(acac)(Lphe)] (Figure4a, in the range of 8.7-7.5 ppm). A similar phenomenon was already observed in the spectra of the Pt(II) complexes of the Schiff base derived from L-phenylalanine and furfuraldehyde[31]. The signals assigned to water protons were much more intensive than those of water absorbed in DMSO d6; this most probably indicated that the synthesized complexes also contained a water molecule, similar to that for Zn[(acac)2 H2O].…”
supporting
confidence: 75%
“…Furthermore, the shift in signals and splitting of protons of the aryl groups were observed, especially in the spectrum of Zn[(acac)(Lphe)] (Figure4a, in the range of 8.7-7.5 ppm). A similar phenomenon was already observed in the spectra of the Pt(II) complexes of the Schiff base derived from L-phenylalanine and furfuraldehyde[31]. The signals assigned to water protons were much more intensive than those of water absorbed in DMSO d6; this most probably indicated that the synthesized complexes also contained a water molecule, similar to that for Zn[(acac)2 H2O].…”
supporting
confidence: 75%
“…The antimicrobial activities of the BBHMP and platinum complex were tested against gram(-) Escherichia coli (ATCC® 25922™), Salmonella typhimurium (ATCC® 14028™), Listeria monocytogenes (ATCC® 19115™) gram (+) Staphylococcus aureus (ATCC® 25923™), Bacillus cereus (ATCC® 11778™), and fungal Candida albicans (ATCC® 1023™). The micro broth dilution method and Clinical and Laboratory Standards Institute (CLSI) [21][22][23][24][25] procedures were used to nd the minimal inhibition concentration values (MIC). To measure the area for zone of inhibition, Ampicillin for bacterial strains and Amphotericin B for fungal strains were chosen as antibiotic (positive control).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The cytotoxicity was determined by MTT assay [25][26][27][28]. The MTT method is a widely used cell viability test for cytotoxicity and can be used with all cancer cell types because it metabolizes all living cells.…”
Section: Mtt Analysis For Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations